Fiber assembly and method for producing the same
A fiber aggregate with a small average diameter is produced using syndiotactic polystyrene through a controlled melt blown process, addressing the thickness and structure issues of SPS nonwoven fabrics, enabling applications in filters and heat-insulating materials.
Patent Information
- Application Number
- JP2020097981
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-06-04
- Publication Date
- 2024-12-23
- Estimated Expiration
- 2040-06-04
AI Technical Summary
Nonwoven fabrics made from syndiotactic polystyrene (SPS) have a large average fiber diameter, resulting in a thick and sparse structure, necessitating improvements for better performance and applications.
A fiber aggregate is produced using syndiotactic polystyrene with a melt blown method, involving the melting and stretching of thermoplastic resin with heated gas through a spinneret, and collecting the fibrous resin on a web former belt, with specific conditions for MFR, temperature, and distance control to achieve a small average fiber diameter.
The resulting fiber aggregate has a small average fiber diameter, enabling applications such as filters for capturing fine particles and requiring heat resistance, as well as use in heat insulating and sound absorbing materials.
Smart Images

Figure 0007604117000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a fiber assembly and a method for producing the fiber assembly. [Background technology]
[0002] Nonwoven fabrics using syndiotactic polystyrene (hereinafter also referred to as "SPS") as a raw material are known (see, for example, Patent Document 1). SPS is generally known to have higher heat resistance than polyolefins. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2016-121283 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, the SPS nonwoven fabric described in Patent Document 1 etc. has a large average fiber diameter, which makes the nonwoven fabric thick and sparse in structure, leaving room for further improvement. Therefore, an object of the present invention is to provide an SPS fiber assembly having a small average fiber diameter and a method for producing the fiber assembly. [Means for solving the problem]
[0005] Specific means for solving the above problems include the following aspects.
[0006] <1> A fiber assembly containing fibers containing syndiotactic polystyrene having an MFR (300°C, load 2.16 kg) of 100g / 10min to 200g / 10min. <2> The average fiber diameter of the fibers is 5 μm or less. <1> The fiber assembly according to claim 1. <3> The thickness is 0.5 mm or less. <1> or <2> The fiber assembly according to claim 1. <4> Weight is 25g / m 2 Below is the <1> ~ <3> The fiber assembly according to any one of claims 1 to 5. <5> It is flocculent, <1> ~ <4> The fiber assembly according to any one of claims 1 to 5. <6> It is a nonwoven fabric. <1> ~ <4> The fiber assembly according to any one of claims 1 to 5. <7> A step of melting a thermoplastic resin containing syndiotactic polystyrene having an MFR (300°C, load 2.16 kg) of 100g / 10min to 200g / 10min; A step of discharging the molten thermoplastic resin together with a heated gas from a spinneret having a plurality of holes and stretching the thermoplastic resin by the heated gas to form a fibrous resin; and collecting the fibrous resin in the form of a web on a web former belt. <8> The flow rate of the heating gas is 250 Nm 3 / hr / m~750Nm 3 / hr / m, <7> A method for producing the fiber assembly according to claim 1. <9> The discharge amount per hole is 5 mg / min to 150 mg / min. <7> or <8> A method for producing the fiber assembly according to claim 1. <10> The melting temperature is 250°C to 400°C. <7> ~ <9> 13. A method for producing a fiber assembly according to claim 12. <11> A pyrolysis step of treating syndiotactic polystyrene having an MFR (300°C, load 2.16 kg) of less than 100 g / 10 min under conditions of 250°C to 400°C and 1 minute to 25 minutes to obtain syndiotactic polystyrene having an MFR (300°C, load 2.16 kg) of 100 g / 10 min to 200 g / 10 min, <7> ~ <10> 13. A method for producing a fiber assembly according to claim 12. <12> The distance between the spinneret and the web former belt is 120 mm or less. <7> ~ <11> 13. A method for producing a fiber assembly according to claim 12. <13> The distance between the spinneret and the web former belt is more than 120 mm. <7> ~ <11> 13. A method for producing a fiber assembly according to claim 12. Effect of the Invention
[0007] According to the present disclosure, there is provided an SPS fiber assembly having a small average fiber diameter and a method for producing the fiber assembly. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, embodiments of the present disclosure will be described. These descriptions and examples are merely illustrative of the embodiments, and are not intended to limit the scope of the embodiments.
[0009] In the present disclosure, a numerical range expressed using "to" means a range that includes the numerical values before and after "to" as the lower and upper limits.
[0010] In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples.
[0011] In the present disclosure, each component may contain multiple types of corresponding substances. When referring to the amount of each component in a composition in the present disclosure, if multiple substances corresponding to each component are present in the composition, the total amount of the multiple substances present in the composition is meant unless otherwise specified.
[0012] <Fiber assembly> The fiber assembly of the present disclosure contains fibers containing syndiotactic polystyrene (SPS) having an MFR (300° C., load 2.16 kg) of 100 g / 10 min to 200 g / 10 min. The fiber assembly of the present disclosure can have a small average fiber diameter while using SPS, which has better heat resistance than polyolefin, by adopting the above-mentioned configuration. By reducing the average fiber diameter, a filter capable of capturing fine particles can be manufactured, and the filter can be used as a filter for boiler exhaust ports and other applications requiring heat resistance. Furthermore, the filter can be applied to insulation and sound-absorbing materials.
[0013] (component) SPS is a polystyrene polymer that has a predominantly syndiotactic structure, which means that the stereochemical structure is a syndiotactic structure, i.e., a stereochemical structure in which the phenyl groups in the side chains are alternately positioned in opposite directions to the main chain formed by carbon-carbon bonds. The tacticity of SPS is quantified by nuclear magnetic resonance (13C-NMR) using carbon isotopes. The tacticity of the syndiotactic structure can be expressed by the proportion of consecutive structural units, for example, dyads in the case of two, triads in the case of three, and pentads in the case of five. Usually, polystyrene polymers having a syndiotacticity of preferably 75% or more, more preferably 85% or more are used as racemic dyads, and polystyrene polymers having a syndiotacticity of preferably 30% or more, more preferably 50% or more are used as racemic pentads.
[0014] The SPS is preferably at least one selected from polystyrene, poly(alkylstyrene), poly(halogenated styrene), poly(halogenated alkylstyrene), poly(alkoxystyrene), poly(vinyl benzoate), and hydrogenated polymers thereof, as well as mixtures of two or more selected from these, and copolymers containing these structural units as the main component.
[0015] Examples of the poly(alkylstyrene) include poly(methylstyrene), poly(ethylstyrene), poly(isopropylstyrene), poly(t-butylstyrene), poly(phenylstyrene), poly(vinylnaphthalene), and poly(vinylstyrene). Examples of the poly(halogenated styrene) include poly(chlorostyrene), poly(bromostyrene), poly(fluorostyrene), and the like. Examples of the poly(halogenated alkylstyrene) include poly(chloromethylstyrene). Examples of poly(alkoxystyrene) include poly(methoxystyrene), poly(ethoxystyrene), and the like.
[0016] Among these, preferred styrene-based polymers include polystyrene, poly(p-methylstyrene), poly(m-methylstyrene), poly(p-,t-butylstyrene), poly(p-chlorostyrene), poly(m-chlorostyrene), poly(p-fluorostyrene), hydrogenated polystyrene, and copolymers containing these structural units, with styrene homopolymers (polystyrene) being particularly preferred.
[0017] One type of SPS may be used alone, or two or more types may be used in combination. However, at least one type of SPS has an MFR (300°C, load 2.16 kg) of 100g / 10min to 200g / 10min. An SPS with an MFR (300°C, load 2.16 kg) of 100g / 10min to 200g / 10min is also called a "specific SPS". The MFR (300° C., load 2.16 kg) of the specific SPS is preferably 110 g / 10 min to 180 g / 10 min, and more preferably 120 g / 10 min to 160 g / 10 min. It is preferable that the MFR (300°C, load 2.16 kg) of the specific SPS is equal to or higher than the lower limit, since the average fiber diameter tends to be smaller. It is also preferable that the MFR (300°C, load 2.16 kg) of the specific SPS is equal to or lower than the upper limit, since the fiber strength tends to be improved and the generation of decomposition components tends to be suppressed.
[0018] The MFR is measured according to ASTM D-1238 (Method B) under the following conditions. The measurement sample is pre-dried at 120°C for 6 hours before measurement. Test method: ASTM D1238 (Method B) ·Filling amount: 8.0g Test temperature: 300℃ Load capacity: 2.16kg The measurement is carried out three times under the above conditions, and the average value is calculated. As the measuring device, for example, a Melt Indexer F-F01 type (Toyo Seiki Seisakusho Co., Ltd.) can be used.
[0019] The specific SPS can be obtained, for example, by pyrolyzing an SPS having a MFR of less than 100 g / 10 min. The pyrolysis will be described in detail later.
[0020] The fibers contained in the fiber assembly may contain other thermoplastic resins besides SPS. As the other thermoplastic resin, a resin having a structural unit compatible with a specific SPS is preferable. For example, there are polymers having a styrene block such as atactic polystyrene, isotactic polystyrene, styrene-butadiene block copolymer (SBR), hydrogenated styrene-butadiene block copolymer (SEB, SEBC), styrene-butadiene-styrene block copolymer (SBS), hydrogenated styrene-butadiene-styrene block copolymer (SEBS), styrene-isoprene block copolymer (SIR), hydrogenated styrene-isoprene block copolymer (SEP), hydrogenated styrene-isoprene-styrene block copolymer (SEPS), and their modified products, polyphenylene ether and its modified product, styrene-isoprene-styrene block copolymer (SIS), acrylonitrile-styrene (AS) resin, acrylonitrile-butadiene-styrene (ABS) resin, and other styrene polymers and styrene elastomers.
[0021] Further examples of other thermoplastic resins include polyester resins such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT); polycarbonate resins; polyphenylene sulfide resins (PPS); polyamide resins such as nylon 6, nylon 6,6, and nylon 4,6; thermoplastic polyimides; polyamideimides; polyether resins such as polyphenylene oxide, polysulfone, and polyethersulfone; acrylic resins such as polyacrylic acid, polyacrylic acid esters, and polymethyl methacrylate; polyolefin resins such as polyethylene, polypropylene, polybutene, poly4-methylpentene-1, ethylene-propylene copolymer, ethylene-acrylic acid copolymer, ethylene-vinyl alcohol copolymer, and ethylene-vinyl acetate copolymer; halogen-containing vinyl compound polymers such as polyvinyl chloride, polyvinylidene chloride, and polyvinylidene fluoride; polyoxymethylene; polyvinyl alcohol resins; polyacetal; amorphous polyarylate; and derivatives thereof. These other thermoplastic resins may be used alone or in combination of two or more.
[0022] The fiber assembly of the present disclosure may contain various known additives, such as antioxidants, heat stabilizers, weather stabilizers, antistatic agents, slip agents, antifogging agents, lubricants, dyes, pigments, natural oils, synthetic oils, waxes, fatty acid amides, etc., as necessary, within the range that does not impair the heat resistance of the fiber assembly. The content of these additives in the fiber assembly is preferably 0.1% by mass or less, more preferably 0.05% by mass or less, and even more preferably 0.01% by mass or less.
[0023] The SPS content in the fiber assembly is preferably 1% by mass to 100% by mass, more preferably 50% by mass to 100% by mass, further preferably 80% by mass to 100% by mass, and particularly preferably 90% by mass to 100% by mass. The content of the specific SPS in the SPS is preferably 50% by mass to 100% by mass, more preferably 90% by mass to 100% by mass, and further preferably 99% by mass to 100% by mass.
[0024] (Mold of fiber assembly) The fiber aggregate of the present disclosure may be composed of long fibers or short fibers, and from the viewpoint of productivity, it is preferable that the fiber aggregate is composed of long fibers. In the present disclosure, "short fibers" refers to fibers having an average fiber length of 200 mm or less. Also, "long fibers" refers to fibers having an average fiber length of more than 200 mm.
[0025] The fiber assembly of the present disclosure may be a nonwoven fabric or a cotton-like fabric. In the present disclosure, "nonwoven fabric" refers to a fiber assembly in which fibers are entangled and fused to each other to form a sheet. In the present disclosure, "cotton-like" refers to a fiber assembly in which fibers are entangled to form a mass. Specifically, when observed under an electron microscope (magnification: ×500), a fiber assembly having a total area of 0.2 mm 2 When there are 50 or more fusion points between fibers within this range, it is called "nonwoven fabric," and when there are less than 50, it is called "cotton-like."
[0026] The fiber assembly of the present disclosure may be a single layer or a laminate in which multiple layers are laminated. The laminate may contain the fiber assembly of the present disclosure in at least one layer of the laminate, and may be, for example, a laminate in which multiple fiber assemblies manufactured by one manufacturing method are laminated, or a laminate in which multiple fiber assemblies manufactured by two or more manufacturing methods are laminated, and may be laminated with a layer other than a nonwoven fabric or a cotton-like layer such as a film. Examples of fiber assemblies and films other than those disclosed in the present disclosure that are laminated include conventionally known fiber assemblies and films.
[0027] [Physical properties of fiber assembly] (Average fiber diameter) In consideration of the intended use, the fiber aggregate preferably has an average fiber diameter of 5 μm or less, more preferably 0.05 μm to 3 μm, and even more preferably 0.1 μm to 2 μm. The smaller the average fiber diameter, the more small particles can be captured when made into a filter, and the thinner the filter can be.
[0028] The average fiber diameter of the fiber assembly can be determined as follows. The surface of the fiber assembly to be measured is photographed at a magnification of 1000 times using an electron microscope (model number: S-3500N, manufactured by Hitachi, Ltd.). From the photograph, 1000 fibers (n=1000) are randomly selected, the diameter (width) of the selected fibers is measured, and the arithmetic average value is calculated as the average fiber diameter (Da).
[0029] The fiber aggregate of the present disclosure has a tendency to have a small average fiber diameter because the MFR of the specific SPS is within a predetermined range. The method for making the average fiber diameter of the fiber aggregate within the above range is not particularly limited, and examples of the method include a method for controlling the spinning temperature, residence time, nozzle hole diameter, single hole discharge amount (discharge amount per nozzle hole), heated air temperature, heated air flow rate, etc. during the production of the fiber aggregate.
[0030] (Thickness) When the fiber assembly is a nonwoven fabric, the thickness of the nonwoven fabric is preferably 0.5 mm or less, more preferably 0.005 mm to 0.5 mm, even more preferably 0.01 mm to 0.3 mm, and particularly preferably 0.02 mm to 0.2 mm. The smaller the thickness, the more small particles can be captured when made into a filter, and the thinner the filter can be.
[0031] The thickness of the fiber assembly can be determined as follows. For the ten fiber assemblies to be measured, the thickness was measured at five points, the center and the four corners, and the average value of the ten points was calculated. The thickness was measured with a load of 7 gf / cm 2 Use a thickness gauge (sensor diameter 25mmφ).
[0032] (Met) The basis weight of the fiber assembly is preferably set appropriately depending on the application, and is generally set to 25 g / m 2 It is preferable that the content is less than 1 g / m 2 ~15g / m 2 More preferably, it is 2 g / m 2 ~8g / m 2 It is even more preferable that:
[0033] When the fiber assembly is a nonwoven fabric, the basis weight of the fiber assembly is 25 g / m 2 It is preferable that the content is less than 1 g / m 2 ~15g / m 2 More preferably, it is 2 g / m 2 ~8g / m 2 It is even more preferable that: When the fiber assembly is used as a filter, the basis weight of the fiber assembly is 25 g / m 2 It is preferable that the content is 2 g / m or less. 2 ~15g / m 2 More preferably, it is 3 g / m 2 ~8g / m 2 It is even more preferable that:
[0034] The weight per unit area of the fiber assembly can be determined as follows. Ten test pieces measuring 100 mm (in the direction of fiber flow: MD) x 100 mm (in the direction perpendicular to the direction of fiber flow (CD)) are taken from the fiber assembly. The test pieces are taken from 10 locations in the CD direction. Next, the mass [g] of each test piece is measured using a top-pan electronic balance (manufactured by Kensei Kogyo Co., Ltd.) to calculate the average mass of each test piece. The mass of each test piece is then subtracted by 1 m from the average value calculated above. 2 The weight per unit area of each fiber aggregate is calculated by converting it into the mass per unit area [g] and the weight per unit area [g / m 2 〕
[0035] The method for adjusting the basis weight of the fiber assembly to the above range is not particularly limited, and examples thereof include a method of changing and adjusting the speed of a collector during the production of the fiber assembly.
[0036] (Breathability) The fiber aggregate is preferably adjusted appropriately depending on the application such as a filter. For example, 3 / cm 2 sec~200cm 3 / cm 2 sec is preferred, and 3 cm 3 / cm 2sec~100cm 3 / cm 2 It is more preferable that the ratio is sec.
[0037] The air permeability of the fiber assembly can be determined as follows. A fiber assembly was prepared, and five test pieces measuring 20 cm x 20 cm were taken from the fiber assembly in a temperature-controlled room at a temperature of 20 ± 2°C and humidity of 65 ± 2% as specified in JIS Z8703 (standard conditions at the test site), in accordance with JIS L1096 (8.27.1A method; Frazier type method). The amount of air passing through the test pieces (cm) was measured using a Frazier type tester. 3 / cm 2 ·sec) and calculate the average value.
[0038] (Tensile strength) The tensile strength of the fiber assembly is preferably 5 N / 50 mm or more, more preferably 5 N / 50 mm to 200 N / 50 mm, and even more preferably 10 N / 50 mm to 100 N / 50 mm.
[0039] The tensile strength of the fiber assembly can be determined as follows. A test piece measuring 50 mm wide x 200 mm long is taken from the fiber assembly to be measured, and a tensile testing machine (Shimadzu Autograph AGS-J) is used to measure 5 points in the longitudinal direction (MD) and 5 points in the transverse direction (CD) with a chuck distance of 100 mm and a head speed of 300 mm / min. The average value is calculated to determine the tensile strength.
[0040] There are no particular limitations on the specific method for making the tensile strength of the fiber assembly fall within the above range. For example, the method may include making the fiber assembly contain polyamide as the thermoplastic resin; or moving the position of a collector belt that collects the fibers after spinning closer to the nozzle.
[0041] (Applications of fiber assemblies) The fiber assembly of the present disclosure is not particularly limited in its application, and can be used for applications known for fiber assemblies. In particular, since the fiber assembly of the present disclosure contains SPS and has excellent heat resistance and can have a small average fiber diameter, it can be suitably used for, for example, filters, sound absorbing materials, heat insulating materials, and the like. The filter can be suitably used in places where heat resistance is required, such as boiler and engine filters. As a sound absorbing or heat insulating material, it can be placed in the space around the engine of a vehicle, or in locations where heat resistance, flame retardancy, etc. are required.
[0042] <Method for manufacturing fiber assembly> The method for producing a fiber assembly according to the present disclosure is a melt-blown production method including the steps of melting a thermoplastic resin containing syndiotactic polystyrene (the above-mentioned specific SPS) having an MFR (300°C, load 2.16 kg) of 100 g / 10 min to 200 g / 10 min (hereinafter also referred to as the "melting step"); discharging the molten thermoplastic resin together with heated gas from a spinneret having a plurality of holes and stretching the thermoplastic resin with the heated gas to form a fibrous resin (hereinafter also referred to as the "discharging step"); and collecting the fibrous resin in the form of a web on a web former belt (hereinafter also referred to as the "collection step"). The method for producing a fiber assembly according to the present disclosure includes the above steps, and thus can produce an SPS fiber assembly having a narrow average fiber diameter.
[0043] The method for producing a fiber assembly according to the present disclosure may include other steps in addition to the steps described above, such as a step of preparing a specific SPS (hereinafter also referred to as a "preparation step").
[0044] (preparation process) The preparation process includes a pyrolysis step in which syndiotactic polystyrene (hereinafter also referred to as "raw SPS") having an MFR (300°C, load 2.16 kg) of less than 100 is treated under conditions of 250°C to 350°C and 1 to 25 minutes to obtain syndiotactic polystyrene (specific SPS) having an MFR (300°C, load 2.16 kg) of 100 g / 10 min to 200 g / 10 min.
[0045] The MFR (300°C, load 2.16 kg) of the raw material SPS is less than 100 g / 10 min, preferably 90 g / 10 min or less, more preferably 80 g / 10 min or less, and even more preferably 70 g / 10 min or less, from the viewpoint of controlling the MFR of the specific SPS obtained by thermal decomposition.
[0046] The temperature in the pyrolysis step of the raw material SPS is 250° C. to 400° C., preferably 270° C. to 400° C., and more preferably 290° C. to 400° C. The higher the temperature in the pyrolysis step, the higher the MFR (300° C., load 2.16 kg) of the obtained specific SPS tends to be.
[0047] The time for the pyrolysis of the raw SPS is 1 to 25 minutes, preferably 3 to 25 minutes, and more preferably 6 to 25 minutes, in the above-mentioned temperature range. The longer the time for the pyrolysis, the higher the MFR (300°C, load 2.16 kg) of the obtained specific SPS tends to be. In the thermal decomposition step of the raw material SPS, heating within the above temperature range may be performed once or may be repeated two or more times. When heating is repeated two or more times, the above-mentioned time refers to the total time within the above temperature range.
[0048] For the thermal decomposition of the raw material SPS, for example, an extruder, a decomposition accelerator (degla agent), etc. can be used.
[0049] In this way, the raw SPS may be thermally decomposed to prepare the specific SPS in advance before carrying out the subsequent melting step, or the raw SPS may be thermally decomposed in the melting step without going through the preparation step.Furthermore, the raw SPS may be thermally decomposed in both the preparation step and the melting step.
[0050] (Melting process) In the melting step, the thermoplastic resin containing the specific SPS is melted. When the specific SPS is obtained by pyrolyzing the raw SPS in the melting step, the melting temperature is preferably 250°C to 400°C, more preferably 300°C to 390°C, and even more preferably 350°C to 380°C. The higher the temperature in the melting step, the higher the MFR (300°C, load 2.16 kg) of the obtained specific SPS tends to be. When the specific SPS obtained in the above-mentioned preparation step is used, the melting temperature in the melting step is preferably 250°C to 400°C, more preferably 270°C to 380°C, and even more preferably 310°C to 350°C.
[0051] The residence time in the melting step is preferably 10 to 100 minutes, more preferably 10 to 60 minutes, and even more preferably 10 to 40 minutes. The longer the residence time in the melting step, the higher the MFR (300°C, load 2.16 kg) of the obtained specific SPS tends to be. The time in the temperature range of 250°C to 400°C is, for example, 1 to 25 minutes, preferably 3 to 25 minutes, and more preferably 6 to 25 minutes. In the melting step, heating in the above temperature range may be performed only once, or may be repeated two or more times. When heating is repeated two or more times, the above time refers to the total time in the above temperature range.
[0052] Furthermore, when a specific SPS is prepared in advance in the preparation step, the melting time (residence time) is not particularly limited and can be appropriately designed depending on the production scale, etc., as long as the thermoplastic resin is sufficiently melted, and specifically, it is preferably 5 to 30 minutes, and more preferably 7 to 20 minutes.
[0053] In the melting step, it is preferable to knead the thermoplastic resin using two or more shafts in order to suppress uneven kneading and knead the thermoplastic resin accurately. The shaft used for kneading is, for example, a screw. The kneading and melting step may be performed using, for example, a melt extruder equipped with two or more screws.
[0054] (Spinning process) A molten thermoplastic resin (hereinafter also referred to as "melt") is discharged together with heated gas from a spinneret having a plurality of holes, and the thermoplastic resin is stretched by the heated gas to form a fibrous resin. Specifically, the melt is pressured using an extruder and supplied to a spinneret having a nozzle formed therein, and the melt is ejected from the nozzle. The extruder is not particularly limited, and may be a single-screw extruder or a multi-screw extruder. The temperature of the melt during spinning (extrusion temperature) is not particularly limited as long as the molten state can be maintained, and may be set within the same temperature range as the melting temperature, for example. The difference between the extrusion temperature and the melting temperature is preferably within -50°C to +50°C, more preferably within -20°C to +20°C.
[0055] The nozzle hole diameter is preferably 0.06 mm to 0.50 mm, and more preferably 0.10 mm to 0.40 mm. The discharge rate per hole in the nozzle (single hole discharge rate) is preferably 5 mg / min to 150 mg / min, more preferably 7 mg / min to 100 mg / min, and further preferably 10 mg / min to 70 mg / min. The temperature of the heating gas is preferably 250°C to 420°C, and more preferably 290°C to 410°C. The flow rate of the heating gas is 250Nm 3 / hr / m~750Nm 3 / hr / m, preferably 630Nm 3 / hr / m~740Nm 3 / hr / m is more preferable. By setting the nozzle hole diameter, discharge rate, and temperature and flow rate of the heated gas within these ranges, the average fiber diameter of the obtained fiber aggregate can be made small, and the generation of resin particles tends to be reduced.
[0056] (Collection process) In the collecting step, the fibrous resin is collected in the form of a web on a web former belt. In the spunbonding method, the fibrous resin is cooled before collection, whereas in the meltblown method, the fibrous resin is collected without being cooled, and therefore the fibers tend to fuse together on the collector. Therefore, the closer the distance between the spinneret and the web former belt, the more the fibers are collected on the web former belt in a fused state, forming a nonwoven fabric. On the other hand, the farther the distance between the spinneret and the web former belt, the more the temperature of the fibrous resin drops before it is collected on the web former belt, and the more the fibers do not fuse together and become cotton-like.
[0057] From the viewpoint of obtaining a nonwoven fabric, the distance between the spinneret and the web former belt is preferably 120 mm or less, more preferably 10 mm to 110 mm, and even more preferably 30 mm to 80 mm. On the other hand, from the viewpoint of obtaining a cotton-like fiber aggregate, the distance between the spinneret and the web former belt is preferably more than 120 mm, more preferably 150 mm to 500 mm, and even more preferably 250 mm to 450 mm.
[0058] The collecting step may be performed while sucking air from the back side of the web former belt, which tends to prevent the fibers from scattering.
[0059] In the collecting step, a collecting material may be placed on the web former belt. The collecting material can be wound up together with the fiber assembly. Examples of the collecting material include nonwoven fabrics other than the nonwoven fabric of the present invention. The use of the collecting material tends to facilitate winding. The collecting material preferably has a basis weight that does not hinder the suction of air.
[0060] (Other processes) The fiber aggregate obtained by collecting and depositing on the web former belt may be further subjected to secondary processing, such as entangling, pressing, gearing, printing, coating, laminating, heating, shaping, hydrophilic, water-repellent, and pressing.
[0061] Examples of the interlacing treatment include heat embossing, ultrasonic fusion, water jet treatment, hot air through treatment, and needle punch treatment. From the viewpoint of maintaining a better balance between rigidity and breathability, it is preferable that the entanglement treatment includes a heat embossing treatment. When the fiber assembly of the present disclosure is thermally bonded by thermal embossing, the embossed area ratio (thermocompression bonded portion) is preferably in the range of 5% to 30%, and more preferably in the range of 5% to 20%. Examples of the imprint shape include a circle, an ellipse, an oval, a square, a diamond, a rectangle, a rectangle, a square, a quilt, a lattice, a tortoiseshell, and a continuous shape based on these shapes.
[0062] From the viewpoint of controlling the thickness, rigidity, density, air permeability, etc. of the fiber assembly of the present disclosure, the secondary processing preferably includes a pressing process. The pressing means for pressing the fiber assembly of the present disclosure in the pressing process is not particularly limited, and may be, for example, a pressing means for pressing the fiber assembly by applying pressure in the thickness direction (in the case where the fiber assembly is a laminate, the lamination direction of the laminate). Examples of the pressing process include a method of press-molding two or more layers of fiber assembly (more preferably a meltblown nonwoven fabric) deposited in a sheet shape; roll molding in which the fiber assembly is pressed by a roll; and the like, and among these, it is preferable to include roll molding. EXAMPLES
[0063] The present invention will be described in more detail below based on examples, but the present invention is not limited to the following examples. The materials, amounts used, ratios, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of this disclosure. In addition, "parts" means "parts by mass" unless otherwise specified.
[0064] --Preparing materials-- The following three types of SPS were used. The MFR of SPS was measured by the method described above. SPS1: Syndiotactic polystyrene (Idemitsu Kosan Co., Ltd., Zarec 300ZC) The MFR at 300°C and a load of 2.16 kg is 67.5 g / 10 min. SPS2: Syndiotactic polystyrene obtained by compounding SPS1 in a twin-screw extruder at 350℃ for 3.6 minutes and pyrolyzing it. The MFR at 300°C and a load of 2.16 kg is 131 g / 10 min. SPS3: Syndiotactic polystyrene obtained by compounding SPS1 in a twin-screw extruder at 350℃ for 7.2 minutes and pyrolyzing it. The MFR at 300°C and a load of 2.16 kg is 156 g / 10 min.
[0065] [Example 1] SPS3 was melted at 320°C, the spinneret temperature was 320°C, the nozzle hole diameter was 0.12mm, the single hole discharge rate was 14mg / min, and the heated air flow rate was 690Nm 3 The material was discharged from the spinneret under the following conditions: flow rate: 300 g / hr / m, heated air temperature: 320°C, distance between the spinneret and the web former belt (hereinafter also referred to as "DCD"): 60 mm, and extrusion temperature: 320°C. The fibrous SPS3 was collected on the web former to obtain a meltblown nonwoven fabric. The resulting meltblown nonwoven fabric had a basis weight of 5 g / m 2 The thickness was 0.10 mm and the average fiber diameter was 1.0 μm. The fibrous SPS in the obtained meltblown nonwoven fabric had an MFR of 180 g / 10 min at 300° C. and a load of 2.16 kg.
[0066] [Example 2] The spinning was performed under the condition that the distance between the spinneret and the web former belt was 300 mm, and the collected material had a basis weight of 13 g / m 2 A cotton-like fiber aggregate was obtained in the same manner as in Example 1, except that the polypropylene spunbond nonwoven fabric was used. The resulting cotton-like fiber aggregate had a basis weight of 5 g / m 2 The average fiber diameter was 1.0 μm. Because it was cotton-like, the thickness was not measured. The fibrous SPS in the obtained cotton-like fiber assembly had an MFR of 180 g / 10 min at 300° C. and a load of 2.16 kg.
[0067] [Example 3] Heated air flow rate: 300Nm 3 A meltblown nonwoven fabric was obtained in the same manner as in Example 1, except that the flow rate was changed to 100 / hr / m, the heated air temperature was 300°C, the melt temperature and extrusion temperature were 300°C, and the distance between the spinneret and the web former belt was 100 mm. The resulting meltblown nonwoven fabric had a basis weight of 10 g / m 2 The thickness was 0.22 mm and the average fiber diameter was 2.2 μm. The fibrous SPS in the obtained meltblown nonwoven fabric had an MFR of 170 g / 10 min at 300° C. and a load of 2.16 kg.
[0068] [Example 4] Using SPS2 instead of SPS3, the nozzle hole diameter is 0.36 mm, the single hole discharge amount is 80 mg / min, and the heated air flow rate is 300 Nm 3 A meltblown nonwoven fabric was obtained in the same manner as in Example 1, except that the flow rate was changed to 100 / hr / m, the heated air temperature was 300°C, the melt temperature and extrusion temperature were 300°C, and the distance between the spinneret and the web former belt was 100 mm. The resulting meltblown nonwoven fabric had a basis weight of 20 g / m 2 The thickness was 0.45 mm and the average fiber diameter was 3.8 μm. The fibrous SPS in the obtained meltblown nonwoven fabric had an MFR of 151 g / 10 min at 300° C. and a load of 2.16 kg.
[0069] [Example 5] In Example 1, SPS2 was used instead of SPS3, the nozzle hole diameter was 0.36 mm, the single hole discharge amount was 120 mg / min, and the heated air flow rate was 300 Nm 3 A meltblown nonwoven fabric was obtained in the same manner as in Example 1, except that the flow rate was changed to 100 / hr / m, the heated air temperature was 300°C, the melt temperature and extrusion temperature were 300°C, and the distance between the spinneret and the web former belt was 100 mm. The resulting meltblown nonwoven fabric had a basis weight of 20 g / m 2 The thickness was 0.48 mm and the average fiber diameter was 4.5 μm. The fibrous SPS in the obtained meltblown nonwoven fabric had an MFR of 144 g / 10 min at 300° C. and a load of 2.16 kg.
[0070] [Comparative Example 1] Using SPS1 instead of SPS3, the nozzle hole diameter is 0.36 mm, the single hole discharge rate is 120 mg / min, and the heated air flow rate is 300 Nm 2 A meltblown nonwoven fabric was obtained in the same manner as in Example 1, except that the melting temperature and extrusion temperature were changed to 300°C, the heating air temperature was changed to 300°C, and the distance between the spinneret and the web former belt was changed to 100 mm. The resulting meltblown nonwoven fabric had a basis weight of 20 g / m 2 The thickness was 0.53 mm and the average fiber diameter was 6.1 μm. The fibrous SPS in the obtained meltblown nonwoven fabric had an MFR of 74 g / 10 min at 300° C. and a load of 2.16 kg.
[0071] [Comparative Example 2] In Example 1, SPS1 was used instead of SPS3, and the single hole discharge amount was 14 mg / min and the flow rate of heated air was 300 Nm 3 / hr / m, the heated air temperature was 300°C, the melt temperature and extrusion temperature were 300°C, and the distance between the spinneret and the web former belt was 100 mm, but melt extrusion was not possible and a nonwoven fabric could not be formed.
[0072] [Table 1]
[0073] As shown in Table 1, the fiber aggregate of the Example had a smaller average fiber diameter than the fiber aggregate of the Comparative Example. The fiber aggregate of the Example used SPS and therefore had excellent heat resistance.
Claims
1. The fiber contains syndiotactic polystyrene having an MFR (300°C, load 2.16 kg) of 100g / 10min to 200g / 10min, The average fiber diameter of the fibers is 5 μm or less, A fiber assembly for use in a heat-resistant filter, sound-absorbing material or heat-resistant material, having a basis weight of 2 g / m 2 to 8 g / m 2 .
2. The fiber assembly according to claim 1, having a thickness of 0.5 mm or less.
3. The fiber assembly according to claim 1 or 2, which is in a cotton-like form.
4. The fiber assembly according to claim 1 or 2, which is a nonwoven fabric.
5. A step of melting a thermoplastic resin containing syndiotactic polystyrene having an MFR (300° C., load 2.16 kg) of 100 g / 10 min to 200 g / 10 min; A step of discharging the molten thermoplastic resin together with a heated gas from a spinneret having a plurality of holes and stretching the thermoplastic resin by the heated gas to form a fibrous resin; and collecting the fibrous resin in the form of a web on a web former belt. A method for producing a fiber assembly using a melt blown method, wherein the discharge amount per hole is 5 mg / min to 150 mg / min.
6. a pyrolysis step of treating syndiotactic polystyrene having an MFR (300°C, load 2.16 kg) of less than 100 g / 10 min under conditions of 250°C to 400°C and 1 minute to 25 minutes to obtain syndiotactic polystyrene having an MFR (300°C, load 2.16 kg) of 100 g / 10 min to 200 g / 10 min; A step of melting the thermoplastic resin containing the syndiotactic polystyrene having an MFR (300° C., load 2.16 kg) of 100 g / 10 min to 200 g / 10 min; A step of discharging the molten thermoplastic resin together with a heated gas from a spinneret having a plurality of holes and stretching the thermoplastic resin by the heated gas to form a fibrous resin; collecting the fibrous resin in the form of a web on a web former belt; A method for producing a fiber assembly using a melt blown method, comprising:
7. The flow rate of the heating gas is 250 Nm 3 / hr / m~750Nm 3 The method for producing a fiber assembly according to claim 5 or claim 6, wherein the fiber length is 1 / hr / m.
8. The method for producing a fiber assembly according to any one of claims 5 to 7, wherein the melting temperature is 250°C to 400°C.
9. The method for producing a fiber aggregate according to any one of claims 5 to 8, wherein a distance between the spinneret and the web former belt is 120 mm or less.
10. The method for producing a fiber aggregate according to any one of claims 5 to 8, wherein a distance between the spinneret and the web former belt is greater than 120 mm.
Citation Information
Patent Citations
Formable sheet and method for forming
JP2000073270A
Nonwoven fabric for electronic component and laminate for the same
JP2000260229A
Molding comprising syndiotactic polystyrene having functional group introduced thereto
JP2016121283A
Biaxially oriented polyarylene sulfide resin film and process for production of same
WO2010143542A1
